Additive manufacturing of 3D structural battery composites with coextrusion deposition of continuous carbon fibers. (October 2020) - Thakur, Aditya; Dong, Xiangyang
Abstract: There is a growing interest in fabrication of structural battery composites to achieve mass-less energy storage. Additive manufacturing would allow customization of their battery form factor to fit specific needs. In this study, a multi-axis coextrusion deposition technique is proposed to fabricate a 3D structural battery composite with continuous carbon fibers coated by solid polymer electrolyte (SPE). The SPE-coated carbon fibers are coextruded with cathode doped matrix materials. All the printed complex structural battery composites successfully power up LEDs. Further mechanical and electrochemical characterization demonstrates the potentials of the additively manufactured composites in electrical energy storage and load bearing.